Against Imperial Violence - the Idea of Planned Polish Emigration according to an Anonymous 19th-Century Document - Dominiak, Łukasz Marcin (Sensus Historiae, 2020)
The text presents the assumptions of the Polish overseas colony project published in 1864. This document appeared in the face of the social crisis caused by the defeat of the January Uprising and the empowerment of the peasants in the Kingdom of Poland. The idea of the planned resettlement of Polish political emigration contains a mixture of its traditional, pre-modern forms and some democratic and ideas of Ultramontanism. A detailed and contextual analysis of this historical evidence leads to valid conclusions on the shaping of a specific pre-modern form of Polish nationalism: exclusive and uniform in confession and politics.